If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 4x + -70 = 0 Reorder the terms: -70 + 2x + 4x = 0 Combine like terms: 2x + 4x = 6x -70 + 6x = 0 Solving -70 + 6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '70' to each side of the equation. -70 + 70 + 6x = 0 + 70 Combine like terms: -70 + 70 = 0 0 + 6x = 0 + 70 6x = 0 + 70 Combine like terms: 0 + 70 = 70 6x = 70 Divide each side by '6'. x = 11.66666667 Simplifying x = 11.66666667
| 6x^2+24x-22=0 | | 3(x+2)+3=2x+10 | | 2x-9=63-10x | | ln(2x-1)=2ln(x) | | 2X-6=2X-5 | | 8ln(5x)=32 | | 6x+6=5x+13 | | x+v=w*2 | | x+5+2(x-1)=x+19 | | 3-5X=2-2X | | x+v=x*2 | | k(-10-7r)= | | .4= | | 12x+5=3+4x | | 4x^2+0x-100=0 | | v+x=x*2 | | 5x-6=x-8 | | 5(a+7b)-35b+5a= | | 63=2.1x | | 1.168=106x | | X-435=97 | | -19=z-3 | | 2(1-4b)+5b=-2(b-1) | | 8x+17=65 | | 4.4=-6+x | | 5e^3x+2=25 | | 3(1+4v)=-3v+6(4+3v) | | 12s^3+14s^2+8s=4s | | X*3-3=12 | | 3x-2+32x+x=21-2+x | | 28x=168 | | 3(2n-1)=-28+n |